Interação entre obesidade induzida por dieta hiperlipídica e colite crônica aumenta reciprocamente a inflamação no tecido adiposo e no cólon - Lilian Gonçalves Teixeira (2012)
Ulcerative colitis is a disease of incompletely understood etiology and is characterized by inflammation of the colonic mucosa. The epidemiology of inflammatory bowel diseases suggests that environmental factors such as personal hygiene, smoking and diet contribute to disease onset. Pro-inflammatory markers including IL- 6, IL-1 and TNF are increased in colitis. These markers are also increased in obesity that have an important inflammatory component too. Obesity is a multifactorial disease involving endocrine factors, genetics and behavior and directly contributes to systemic inflammation. Studies have suggested that adipokines secreted by adipose tissue (leptin, resistin and adiponectin) are closely associated with inflammatory bowel diseases such as ulcerative colitis. In addition, some studies have shown increased pro-inflammatory cytokines in the intestine of obese animals as well as in the adipose tissue of animals with colitis. The objective of this study was to elucidate the relationship between obesity induced by a hypercaloric, high-fat diet (HFD) and chronic colitis induced by intermittent administration of dextran sodium sulfate (DSS). To this, the animals were divided into 4 groups (control, colitis, HFD and colitis + HFD). Mice with chronic colitis induced by 2 cycles of dextran sodium sulfate (DSS) in the first and fourth week of the experiment were fed a high-fat diet (HFD) to induce obesity by 8 weeks. After 8 weeks of experiment, the animals were euthanized, and serum, colon, adipose tissue, spleen and cecal and mesenteric lymph nodes were analysed. Obesity alone did not raise histopathology scores, but the combination of obesity and colitis worsened the scores in the colon compared to colitis group. Despite the reduction in weight gain, there was increased inflammatory infiltrate in both the colon and visceral adipose tissue of colitis + HFD mice due to increased infiltration of macrophages, neutrophils and lymphocytes. Intravital microscopy of VAT microvasculature showed an increase in leukocyte adhesion and rolling and the real time pcr showed overexpression of adhesion molecules compared to other groups. Moreover, we observed increased intestinal permeability and toll like receptor (TLR)4 and leptin receptor expression in the colon of the Colitis+HFD group. The serum leptin were increased only in HFD group. We hypothesized that leptin-receptor (Ob-Rb) binding increasing the inflammation of the colon of Colitis+HDF. Still, circulating lymphocytes, monocytes and neutrophils in the spleen and cecal lymph nodes were increased in the colitis + HFD group. Our results demonstrated the relationship between cronic colitis and obesity as aggravating factors for each disease, with increased inflammation in the colon and adipose tissue and systemic alterations observed in the spleen, lymph nodes and bloodstream.